Study of cobalt effect on structural and optical properties of Dy doped ZnO nanoparticles - Kumar P.; Pandey P.C. (My University, 2025)
The present study has been carried out to investigate the effect of Co doping on structural and optical properties of Dy doped ZnO nanoparticles. We have prepared pure Zinc oxide, Dy (1%) doped ZnO and Dy (1%) doped ZnO co-doped with Co(2%) with the help of simple sol-gel combustion method. The structural analysis carried out using X-ray diffraction spectra (XRD) indicates substitution of Dy and Co at Zn site of ZnO crystal structure and hexagonal crystal structure without any secondary phase formation in all the samples. The surface morphology was analyzed by transmission electron microscopy (TEM). Absorption study indicates that Dy doping causes a small shift in band edge, while Co co-doping results significant change is absorption edge as well as introduce defect level absorption in the visible region. The band gap of samples decreases due to Dy and Co doping, which can be attributed to defect level formation below the conduction band in the system. © 2018 Author(s).